Antipleuritic and Vascular Permeability Inhibition of the Ethyl Acetate-Petroleum Ether Stem Bark Extract of Maerua angolensis DC (Capparaceae) in Murine - Felix Agyei Ampadu; Eric Boakye-Gyasi; Newman Osafo; Charles Kwaku Benneh; Edmund Ekuadzi; Eric Woode (International Journal of Inflammation)
Maerua angolensis has been used traditionally in the management of pain, arthritis, and rheumatism in Ghana and Nigeria but no scientific evidence is currently available to give credence to its folkloric use. The aim of this study was therefore to evaluate the anti-inflammatory effects of a stem bark extract of Maerua angolensis DC (MAE) in acute inflammatory models. The effects of MAE (30-300 mg kg−1) on neutrophil infiltration, exudate volume, and endogenous antioxidant enzymes in lung tissues and lung morphology were evaluated with the carrageenan induced pleurisy model in Sprague Dawley rats. The effects of MAE (30-300 mg kg−1) on vascular permeability were also evaluated in the acetic acid induced vascular permeability in ICR mice. MAE significantly reduced neutrophil infiltration, exudate volume, and lung tissue damage in carrageenan induced pleurisy. MAE increased the activities of antioxidant enzymes glutathione, superoxide dismutase, and catalase in lung tissues. The extract was also able to reduce myeloperoxidase activity and lipid peroxidation in lung tissues in carrageenan induced rat pleurisy. Vascular permeability was also attenuated by the extract with marked reduction of Evans blue dye leakage in acetic acid induced permeability assay. The results indicated that Maerua angolensis is effective in ameliorating inflammation induced by carrageenan and acetic acid. It also has the potential of increasing the activity of endogenous antioxidant enzymes.